Effects of BDNF polymorphism and physical activity on episodic memory in the elderly: a cross sectional study. Issue 1 (December 2015) - Canivet, Anne; Albinet, Cédric; André, Nathalie; Pylouster, Jean; Rodríguez-Ballesteros, Montserrat; Kitzis, Alain; Audiffren, Michel
Abstract Background The brain-derived neurotrophic factor (BDNF) concentration is highest in the hippocampus compared with that in other brain structures and affects episodic memory, a cognitive function that is impaired in older adults. According to the neurotrophic hypothesis, BDNF released during physical activity enhances brain plasticity and consequently brain health. However, even if the physical activity level is involved in the secretion of neurotrophin, this protein is also under the control of a specific gene. The aim of the present study was to examine the effect of the interaction between physical activity andBDNF Val66Met (rs6265), a genetic polymorphism, on episodic memory. Methods Two hundred and five volunteers aged 55 and older with a Mini Mental State Examination score ≥ 24 participated in this study. Four groups of participants were established according to their physical activity level and polymorphism BDNF profile (Active Val homozygous, Inactive Val homozygous, Active Met carriers, Inactive Met carriers). Episodic memory was evaluated based on the delayed recall of the Logical Memory test of the MEM III battery. Results As expected, the physical activity level interacted with BDNF polymorphism to affect episodic memory performance (p < .05). The active Val homozygous participants significantly outperformed the active Met carriers and inactive Val homozygous participants. Conclusion This study clearly demonstrates an interaction between physical activity andBDNF Val66Met polymorphism that affects episodic memory in the elderly and confirms that physical activity contributes to the neurotrophic mechanism implicated in cognitive health. The interaction shows that only participants with Val/Val polymorphism benefited from physical activity.